Design automóvel : novo conceito para um modelo no grupo Volkswagen - Duarte, Nuno Miguel Oliveira, 1984- (2015)
This study intends to present a new concept to a model in the Volkswagen Group, a niche market where the brand isn’t present but has the potential to strengthen the goal of becoming the number one automotive manufacturer. To introduce is important to addresses the automotive history since the birth until today, where we understand which models were important and for what reasons. We also understand that in Portugal in spite of the great amount of auto enthusiasts the tradition of automotive production is much recent than in other countries. Then we study the history of automotive design, were we analyze the cars by their shapes and lines. In this short description we distinguish the company’s or studios that dominate for long decades this thematic. As to expect in this company’s, as in the automotive brands, work designers that search to marvel with prototypes and following production models. There is still a short description of the Volkswagen history, from the first start and how they will fulfil the objective of becoming the largest automotive production group worldwide. We analyze as well the platform MQB that is present in the vehicles of the brand and will be common to all models of the group. At last the proposal of a new model for Volkswagen is presented, starting the work with the body shell type and in which platform will it adapt better. Through the research previously done and in mind the prototypes presented by Volkswagen in the last Auto Shows, we present sketches and a descriptive memory of the propose Roadster